(Re)membering in the Pedagogical Work of Black and Brown Teachers: Reclaiming Stories as Culturally Sustaining Practice. (July 2020) - Gardner, Roberta Price; Osorio, Sandra Lucia; Carrillo, Sara; Gilmore, Rachel
This article centers the memories and identities of Black and Brown teachers as they (re)engage with their school experiences. King and Swartz define (re)membering as the process of reconnecting knowledge of the past. We feature two stories—The first is from Roberta and Rachel who demonstrate how Black women reclaim voice, agency, and their own narratives. The second is Sandra and Sara's as they (re)member their journeys as Latina, bilingual teachers in schools that often diminished and even erased their cultural heritages. We resist the current systematic arrangements that render certain children, schooling contexts, and Black and Brown teachers invisible and left scrambling for their past.